2004
DOI: 10.1007/s10288-003-0024-4
|View full text |Cite
|
Sign up to set email alerts
|

Ten notes on equal-processing-time scheduling

Abstract: Equal-processing-time scheduling problems whose complexity status has been unknown are shown to be solved in polynomial time by well-known and relatively new techniques. Single-machine, parallel-machine, parallel-batch, openshop, flow-shop and job-shop environments are touched upon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 22 publications
0
36
0
Order By: Relevance
“…In [2], a polynomial time algorithm with the complexity O(n 6m+1 ) was proposed for problem P m | r j , p j = p | w j U j . The algorithm is based on the following observations and definitions:…”
Section: 115mentioning
confidence: 99%
See 1 more Smart Citation
“…In [2], a polynomial time algorithm with the complexity O(n 6m+1 ) was proposed for problem P m | r j , p j = p | w j U j . The algorithm is based on the following observations and definitions:…”
Section: 115mentioning
confidence: 99%
“…3.4 It has been noted in [2] that the algorithm developed in [28] for problem R | r j , pmtn | Lmax can be used to solve both problem P | p j = p, pmtn | U j and problem Q | p j = p, pmtn | U j in polynomial time. 3.5 Problem P | r j , p j = p, pmtn | U j is unary NP-hard [20].…”
Section: In [28]mentioning
confidence: 99%
“…Baptiste (1999) gives a polynomial time algorithm for the 1|r j , p j = p| w j U j problem based on dynamic programming. In Baptiste et al (2004) ten equal-processing-time scheduling problems are shown to be solvable in polynomial time, among which is the P m|r j , p j = p| w j U j problem. An overview of more problems with equal processing times can be found in Leung (2004).…”
Section: Introductionmentioning
confidence: 99%
“…This reduction is based on a construction presented by Baptiste at al. [3] who consider the problem P m |r i , p i = 1, chains| f i .…”
Section: Equal Consumption Of Convertersmentioning
confidence: 99%